GLP-1 and GLP-2 act in concert to inhibit fasted, but not fed, small bowel motility in the rat - (:unkn) unknown (My University, 2002)
Small bowel motility was studied in rats at increasing (1-20 pmol/kg/min) intravenous doses of either glucagon-like peptide-1 (GLP-1) or glucagon-like peptide-2 (GLP-2) alone, or in combination in the fasted and fed state. There was a dose-dependent inhibitory action of GLP-1 on the migrating myoelectric complex (MMC), where the dose of 5 pmol/kg/min induced an increased MMC cycle length. No effect was seen with GLP-2 alone, but the combination of GLP-1 and GLP-2 induced a more pronounced inhibitory effect, with significant increase of the MMC cycle length from a dose of 2 pmol/kg/min. During fed motility, infusion of GLP-1 resulted in an inhibition of spiking activity compared to control. In contrast, infusion of GLP-2 only numerically increased spiking activity compared to control, while the combination of GLP-1 and GLP-2 resulted in no change compared to control. In summary, this study demonstrates an additive effect of peripheral administration of GLP-1 and GLP-2 on fasted small bowel motility. In the fed state, GLP-1 and GLP-2 seem to display counter-balancing effects on motility of the small intestine.
Keywords: Animals; Male; Fasting; Rats; Peptide Fragments; Rats, Sprague-Dawley; Insulin; Blood Glucose; Drug Interactions; Glucagon-Like Peptide 1; Peptides; Eating; Electromyography; Gastrointestinal Motility; Glucagon; Glucagon-Like Peptide 2; Injections, Intravenous; Intestine, Small; Protein Precursors